On the nightglow polarisation for space weather exploration - Bosse, Léo; Lilensten, Jean; Gillet, Nicolas; Rochat, Sylvain; Delboulbé, Alain; Curaba, Stephane; Roux, Alain; Magnard, Yves; Johnsen, Magnar Gullikstad; Løvhaug, Unni Pia; Amblard, Pierre-Olivier; Le Bihan, Nicolas; et al. (Journal of Space Weather and Space Climate, 2020)
We present here observations of the polarisation of four auroral lines in the auroral oval and in the polar cusp using a new ground polarimeter called Petit Cru . Our results confirm the already known polarisation of the red line, and show for the first time that the three other lines observed here (namely 557.7 nm, 391.4 nm and 427.8 nm) are polarised as well up to a few percent. We show that in several circumstances, this polarisation is linked to the local magnetic activity and to the state of the ionosphere through the electron density measured with EISCAT. However, we also show that the contribution of light pollution from nearby cities via scattering can not be ignored and can play an important role in polarisation measurements. This series of observations questions the geophysical origin of the polarisation. It also leaves open its relation to the magnetic field orientation and to the state of both the upper atmosphere and the troposphere.